Tissue factor expressed by circulating cancer cell‐derived microparticles drastically increases the incidence of deep vein thrombosis in mice. (8th June 2015) - Thomas, G. M.; Brill, A.; Mezouar, S.; Crescence, L.; Gallant, M.; Dubois, C.; Wagner, D. D.
Summary Background The risk of thrombotic complications such as deep vein thrombosis (DVT) during tumor development is well known. Tumors release into the circulation procoagulant microparticles (MPs) that can participate in thrombus formation following vessel injury. The importance of this MP tissue factor (TF) in the initiation of cancer‐associated DVT remains uncertain. Objective To investigate how pancreatic cancer MPs promote DVT in vivo. Methods We combined a DVT mouse model in which thrombosis is induced by flow restriction in the inferior vena cava with one of subcutaneous pancreatic cancer in C57BL/6J mice. We infused high‐TF and low‐TF tumor MPs to determine the importance of TF in experimental cancer‐associated DVT. Results Both tumor‐bearing mice and mice infused with tumor MPs subjected to 3 h of partial flow restriction developed an occlusive thrombus; fewer than one‐third of the control mice did. We observed that MPs adhered to neutrophil extracellular traps (NETs), which are functionally important players during DVT, whereas neither P‐selectin nor glycoprotein Ib were required for MP recruitment in DVT. The thrombotic phenotype induced by MP infusion was suppressed by hirudin, suggesting the importance of thrombin generation. TF carried by tumor MPs was essential to promote DVT, as mice infused with low‐TF tumor MPs had less thrombosis than mice infused with high‐TF tumor MPs. Conclusions TF expressed on tumor MPs contributes to the increased incidence of cancer‐associated venous thrombosis in mice in vivo. These MPs may adhere to NETs formed at the site of thrombosis.